Ambient-Stable Two-Dimensional Titanium Carbide (MXene) Enabled by Iodine Etching - Shi, Huanhuan; Zhang, Panpan; Liu, Zaichun; Park, Sangwook; Lohe, Martin R.; Wu, Yuping; Shaygan Nia, Ali; Yang, Sheng; Feng, Xinliang (Angewandte Chemie International Edition, 2021)
MXene (e.g., Ti3C2) represents an important class of two-dimensional (2D) materials owing to its unique metallic conductivity and tunable surface chemistry. However, the mainstream synthetic methods rely on the chemical etching of MAX powders (e.g., Ti3AlC2) using hazardous HF or alike, leading to MXene sheets with fluorine termination and poor ambient stability in colloidal dispersions. Here, we demonstrate a fluoride-free, iodine (I2) assisted etching route for preparing 2D MXene (Ti3C2Tx, T=O, OH) with oxygen-rich terminal groups and intact lattice structure. More than 71 % of sheets are thinner than 5 nm with an average size of 1.8 μm. They present excellent thin-film conductivity of 1250 S cm−1 and great ambient stability in water for at least 2 weeks. 2D MXene sheets with abundant oxygen surface groups are excellent electrode materials for supercapacitors, delivering a high gravimetric capacitance of 293 F g−1 at a scan rate of 1 mV s−1, superior to those made from fluoride-based etchants (<290 F g−1 at 1 mV s−1). Our strategy provides a promising pathway for the facile and sustainable production of highly stable MXene materials.
CRIS-Team Scopus Importer:2023-03-20
Keywords: etching; iodine; MXene; stability; two-dimensional materials